Effectiveness of Virtual Reality among Patients with Cardiopulmonary Disorders- A Narrative Review (Literature Review) - Agrawal, Maitrayee; Gujral, Tanya; Kumar Sharma, Chhavi; Zafar, Shahiduz; Sidiq, Mohammad (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Cardiopulmonary disorders, including chronic obstructive pulmonary disease (COPD), heart failure, and post-cardiac surgery conditions, significantly impact patients’ physical capabilities and quality of life. Traditional rehabilitation programs often face challenges such as low motivation and adherence. Virtual Reality (VR), with its immersive and interactive features, has emerged as a potential tool to enhance engagement and improve clinical outcomes in cardiopulmonary rehabilitation. Aim. This narrative review aims to explore the effectiveness of VR-based interventions in the rehabilitation of patients with cardiopulmonary disorders by analyzing current evidence and clinical applications. Materials and Methods. A comprehensive literature search was conducted using databases such as PubMed, Scopus, and Google Scholar. Studies focusing on the use of VR in patients with cardiopulmonary conditions were selected, including randomized controlled trials, observational studies, and pilot trials published in English. Key outcomes assessed included physical performance, respiratory function, psychological well-being, and adherence. Results. The review indicates that VR-based rehabilitation programs can lead to improvements in exercise tolerance, pulmonary function, and mental health indicators such as anxiety and depression. VR also shows promise in enhancing motivation and compliance, especially in home-based and tele-rehabilitation settings. Despite positive trends, heterogeneity in study design, VR modalities, and outcome measures limit definitive conclusions. Conclusions. VR represents a promising adjunct to conventional cardiopulmonary rehabilitation strategies. It offers a novel approach to patient engagement and functional improvement. However, more standardized, large-scale studies are necessary to validate its efficacy and establish clinical protocols for widespread use.